The Importance of Including the Geoid in Terrestrial Survey Data Reduction to the Geocentric Datum of Australia - Featherstone, Will (The Institution of Surveyors, Australia Inc., 1997)
The complete reduction of terrestrial survey data to the Geodetic Reference System 1980 (GRS80) spheroid will become an important consideration after the implementation of the Geocentric Datum of Australia (GDA). Three examples are used to illustrate that when survey data reduction does not incorporate the effects of the Earth's gravity field, errors of approximately 11ppm, 200m and 3" can be introduced into terrain distances, astrogeodetically determined coordinates and azimuths respectively.